Inimitability of al-Rahman in Surah Maryam - Berhanuddin, Qaziah Fatihah (2023)
Understanding the Quran through the names of Allah requires a deeper look into the thematic-structural study of the Quran itself. This study aims at the outcome of a refined understanding of one of Allah’s names; al-Rahman, and its correlation with Surah Maryam. Often, people see the connection to Allah through His names or attributes as a means to increase their spiritual remembrance of Him. However, it does not magnify the reality of Allah’s attribute especially when reading a certain Surah. Thus, through the name of al-Rahman, this research focuses on its visibility in Chapter 19 of the Quran with three objectives; investigating the definition of the word al-Rahman in general and in the Quran, analysing the correlation between the word al-Rahman and Surah Maryam, and discovering a refined understanding of the inimitability of al- Rahman in Surah Maryam. The selection of al-Rahman as the subject of scrutiny is based on its 16 times appearance in the surah which is the most mentioned name of Allah in a particular Quranic chapter. Following Farahi’s theory of al- Naẓm, this research will use its major elements; words chosen, the ʿamūd, and the grouping of the surah as the analytical tools where the refined understanding of al-Rahman is unveiled within the existing theme of Surah Maryam. Finally, this research comes to conclude that Ibrahim’s foundation of faith – analysed from his conversation with his father where the word al-Rahman is mentioned – is accurate to become the central point of Surah Maryam based on this thematicstructural interpretation. Subsequently, this finding also leads to the discovery of al-Rahman in Surah Maryam as the possible indicator of the existence of an organic order in the whole Quran. Furthermore, the research contributes scientifically to a new perspective on the Quran with Quran’s interpretation by exposing the correlation between a name of Allah and a single Surah.